Türkiye’nin Gümrük Birliği’ne geçişi ve gümrük birliği’nin Türk dış ticaretindeki yansıması (1990-2009) - Şençalar, Ali İhsan (My University, 2013)
Yıllardır Türkiye’nin öncelikli hedeflerinden birisi, Avrupa Birliği’ne (AB) tam üye olmaktır. Bu süreç ışığında AB ile Türkiye arasında 6 Mart 1995 yılında Gümrük Birliği Anlaşması imzalanmıştır. Gümrük Birliği’ne girişle birlikte tam üyelik yolunda adım atılmıştır. Türkiye’nin GB’ye girişindeki en önemli özelliği, AB’nin tam üyeliğe kabul etmeden GB aşamasına aldığı ilk ve tek ülke olmasıdır. Bu çalışmanın amacı; Türkiye’nin AB’ye tam üyelik sürecinde önüne getirilen GB şartı karşısında göstermiş olduğu, GB’ye girişi için hazırlık aşamaları ve GB’nin Türkiye ekonomisi üzerine etkilerinin incelenmesidir. Türkiye, GB’ye girerken, AB ülkeleri ile olan dış ticaret hacminin artması ve diğer ülkelere karşı pazar payının korunması gibi kazançlar hedeflemiştir. AB’ye olan ihracatın büyük ölçüde artacağı beklentisi gerçekleşmemiş tam tersine ithalattaki artış sayesinde dış ticaret açığı giderek artmıştır. Bununla birlikte, Türkiye’nin GB’ye girmesiyle üçüncü ülkelerle yaptığı ticaret işlemleri AB gözetimi ve denetimi altına girmiştir. careti, Avrupa Birliği, Ekonomik Entegrasyon

For many years, one of the primary targets of Turkey is to be a full member of the European Union (EU). Under the light of this process, Customs Union Agreement was signed on the 6th March 1995 by and between EU and Turkey. By entering in the Customs Union Turkey took a step toward full membership. The most significant characteristic of entry of Turkey in the Customs Union is that Turkey is the first and only country included in Customs Union stage by EU prior to accepting Turkey for full membership. The purpose of this study is examining the preparatory stages for entry in the Customs Union against the condition of Customs Union imposed on Turkey within the process of full membership as well the effects of the Customs Union on Turkish economy. Turkey targeted at gains including increase of foreign trade volume with EU countries and preservation of its market share against other countries while entering in the Customs Union. The expectation for increase in export to EU was not achieved; on the contrary owing to the increase in import the foreign trade deficit increased gradually. Nevertheless, upon entry of Turkey in the Customs Union the trade transactions performed by Turkey with third countries were put in surveillance and inspection of EU. Key Words: the Customs Union, Turkish Foreign Trade, European Union, Economic Integration
Keywords: Avrupa Birliği; Ekonomi; Gümrük Birliği; Türkiye